A Reflection upon the Station of the Intellect in the Matrix of Religious Understanding - Àyatullah JawÁdi Àmuli (حکمت اسرا)
The relation between ‘reason’ and ‘faith’ or between ‘science’ and ‘religion’ is a subject that has occupied the minds of thinkers for a very long time, giving rise to many and various views. One of the most important and novel views in this regard is the one posited by ÀyatullÁh JawÁdÐ ÀmulÐ in his book The Station of the Intellect in the Matrix of Religious Understanding. After the publication of this book an article, titled “The Position of the Intellect and Revelation in the Matrix of Human Understanding,” appeared in the journal Philosophical Knowledge, no. 24, which raised certain questions about the book and suggested points for further consideration. The present treatise contains explanations that respond to the questions and points raised in the aforementioned article. Editor-in-Chief